Physics-informed machine learning for microscopy - Xypakis Emmanouil; deTurris Valeria; Gala Fabrizio; Ruocco Giancarlo; Leonetti Marco (EPJ Web of Conferences, 2022)
We developed a physics-informed deep neural network architecture able to achieve signal to noise ratio improvements starting from low exposure noisy data. Our model is based on the nature of the photon detection process characterized by a Poisson probability distribution which we included in the training loss function. Our approach surpasses previous algorithms performance for microscopy data, moreover, the generality of the physical concepts employed here, makes it readily exportable to any imaging context.